Electric-bicycle-related injury: a rising traffic injury burden in China. Issue 6 (24th June 2010) - Feng, Zhiying; Raghuwanshi, Rakesh P; Xu, Zigang; Huang, Dayong; Zhang, Chong; Jin, Tao
Abstract : Objective: To examine the rising casualty rate related to electric bicycle usage. Design: Analysis of the Hangzhou Police Bureau's data on electric-bicycle-related injuries and deaths. Setting: Hangzhou, China, 2004–2008. Patients or subjects: Electric-bicycle riders. Main outcome measure: Electric-bicycle-related casualty rates in Hangzhou from 2004 to 2008. Results: There was a significant average annual increase in electric-bicycle-related casualty rates of 2.7 per 100 000 population (95% CI 1.5 to 3.9, p=0.005). At the same time, overall road traffic and manual-bicycle-related deaths and injuries decreased. Conclusion: As it is difficult to ban the use of electric bicycles in China, laws, rules and regulations need to be reinforced and strengthened. New regulations should be created for the safety of electric bicycle riders and others on the road, and mandatory helmet use should be considered.